2022
DOI: 10.1084/jem.20211538
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β promotes stem-like T cells via enforcing their lymphoid tissue retention

Abstract: Stem-like CD8+ T cells sustain the antigen-specific CD8+ T cell response during chronic antigen exposure. However, the signals that control the maintenance and differentiation of these cells are largely unknown. Here, we demonstrated that TGF-β was essential for the optimal maintenance of these cells and inhibited their differentiation into migratory effectors during chronic viral infection. Mechanistically, stem-like CD8+ T cells carried a unique expression pattern of α4 integrins (i.e., α4β1hi and α4β7lo) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Given the elevated expression of HIF-1α and its target genes in Tpex and transitory T cells during chronic viral infection, we speculate that HIF-1a signaling initiates terminal T cell differentiation via transcriptional-metabolic reprogramming from mitochondrial respiration to aerobic glycolysis. This notion is supported by recent studies demonstrating a decisive role of TGF-ý in maintaining Tpex cells 25, 66, 67 . TGF-ý inhibits the transition of Tpex into terminally differentiated Tex cells by suppressing mechanistic target of rapamycin (mTOR) and glycolytic reprogramming 25, 66, 68 .…”
Section: Discussionsupporting
confidence: 53%
“…Given the elevated expression of HIF-1α and its target genes in Tpex and transitory T cells during chronic viral infection, we speculate that HIF-1a signaling initiates terminal T cell differentiation via transcriptional-metabolic reprogramming from mitochondrial respiration to aerobic glycolysis. This notion is supported by recent studies demonstrating a decisive role of TGF-ý in maintaining Tpex cells 25, 66, 67 . TGF-ý inhibits the transition of Tpex into terminally differentiated Tex cells by suppressing mechanistic target of rapamycin (mTOR) and glycolytic reprogramming 25, 66, 68 .…”
Section: Discussionsupporting
confidence: 53%
“…Importantly, our findings emphasize the two unique features of TDLNs in tumor immunotherapies, i.e., (1) TDLNs function as a reservoir to host stemlike T cells and (2) TDLNs function as a trap to limit the active migration/differentiation of stem-like T cells. Similar to tumor settings, we have recently demonstrated that TGF-β promotes the retention of stem-like CD8 + T cells inside lymphoid follicles during chronic viral infection 50,51 . Thus, the TGF-β-dependent lymphoid tissue residency program is not tumor-specific and may represent a universal feature for Tcf-1 + CD8 + T cells.…”
Section: Discussionmentioning
confidence: 94%
“…First, TGF-β restrains mTOR (Mammalian Target of Rapamycin) activity in stem-like T cells to maintain their long-term responsiveness ( 64 ). Second, TGF-β directly suppress the differentiation of CX3CR1 + effector T cells and promotes the formation of CD101 + terminally exhausted T cells ( 64 , 66 , 67 ). Importantly, the impacts of TGF-β are significantly enhanced during the later stages of chronic infection ( 66 ).…”
Section: Lymphoid Residency Of Stem-like T Cells—chronic Infectionmentioning
confidence: 99%
“…Forcing TGF-βR deficient stem-like T cells to stay inside lymphoid follicles via integrin α4 blocking partially corrects the defects. This result suggests that manipulating the location of Tcf-1 + T cells alone is sufficient to control their differentiation ( 67 ).…”
Section: Lymphoid Residency Of Stem-like T Cells—chronic Infectionmentioning
confidence: 99%